PENINGKATAN KUALITAS PELAYANAN POSYANDU MELALUI PERBAIKAN SARANA DAN PRASARANA DI POSYANDU RT. 34 KELURAHAN SEPINGGAN BARU - Fitria, Aliya; Lhara Sari, Oryza; Situmorang, Raftonado (JICS : Journal Of International Community Service, 2024)
The Student Program Mengabdi Desa (PMMD) is an initiative that allows students to be actively involved in community service activities, with the main goal of empowering them through hands-on experience in interacting with communities at the local level. One of the focal points of this program is Posyandu RT. 34 Sepinggan Baru which is located in Sepinggan Baru Urban Village, South Balikpapan District. This Posyandu faces a number of problems which include the lack of optimization of existing resources, safety issues for children, as well as deficiencies in terms of aesthetics and comfort of existing facilities. Seeing these conditions, the step taken is to propose a solution in the form of improving the quality of Posyandu facilities and infrastructure. This will include the construction of a reading corner that is expected to increase the reading interest of Posyandu children and the surrounding community, the implementation of a waste sorting system to increase environmental awareness, as well as physical improvements that include covering drainage and rearranging the layout of the building. The main objectives of this activity are to improve the services provided by Posyandu, stimulate literacy interest among children, and increase environmental awareness in the local community. The expected output targets are the writing of a journal documenting the process and results of Posyandu improvements, the making of an aftermovie that visualizes the activities and their impact, and articles published by the Institute for Research and Community Service (LPPM) that summarize the overall process and results that have been achieved in order to provide useful information for related parties and the general public.